The essence of capital in economics - KoÅ›nik, Anita (SPC Journal of Social Sciences, 2020)
Capital is one of the most important economic categories of modern market economy, related to the economic activity of entities. The concept of "capital" is a very complex, controversial issue, it exists in many meanings and contexts. Has many definitions. Nowadays, we can call everything capital because it is an abstract term. Capital is an essential element of any enterprise. It can be classified in different ways. It is most often grouped into physical, financial and human capital. Human capital is one of the most important factors influencing the development of a company, so it also has a strong impact on the development of national economies. This article presents the definition of human capital by G. Åukasiewicz.Â Â